The features of complex therapy of bacterial vaginosis in pregnant women with cervical incompetence - Д. Г. Коньков; Н. В. Адамчук; В. В. Кливак (Репродуктивная эндокринология, 2020)
Objective of the study: to study the clinical and laboratory efficacy of the Femivag® (contains Lactobacillus gasseri, Lactobacillus rhamnosus) drug in the complex treatment of bacterial vaginosis (BV) in pregnant women with high risk of preterm birth.